Hubungan Pemberian ASI Eksklusif Dengan Kejadian Stunting Pada Balita Umur 12-59 Bulan di Puskesmas Sialang Buah Teluk Mengkudu Kabupaten Serdang Bedagai Tahun 2022 - Effy Marlina Tampubolon; Rosmega , Rosmega; Zulkarnain Batubara (Lembaga Pengembangan Kinerja Dosen, 2023)
Stunting is a growth disorder that the child’s body length is less than -2 standard deviations. Stunting is associated with nutritional adequacy in the first day of life, one of which is exclusive breastfeeding. The aim of this study is to investigate the relationship between exclusive breastfeeding and incidence of stunting among Childs aged 12-59 months. This study was analytical observational with cross sectional design and conducted in Primary Health Center of Sialang Buah on April 2022. The sample of 52 Children was chosen through Total sampling. The results of revealed that 20% respondents were breastfed and 80% were not exclusively breastfed. The prevalence of stunting were 30,91%. Of 34 cases of stunting, 26 respondents did not get exclusive breastfed (88%) and 8 respondents got exclusive breastfed history (22%). Bivariate analysis using Chi-square obtained p = 0,536 (p > 0,05), showed that there was no relationship between exclusive breastfeeding and prevalence of stunting.